PENGARUH PAPARAN PESTISIDA TERHADAP KADAR KADMIUM PADA SAMPEL DARAH PETANI DI DUSUN CANGAR DESA BULUKERTO KECAMATAN BUMI AJI KOTA BATU - Syarifatul Qomariyah (Jurnal Kedokteran Komunitas, 2018)
Introduction: The use of pesticides can control the growth of plant pests and increase agricultural production. Nonetheless, pesticides also can cause heavy metal contamination in the environment. Cadmium is a heavy metal contained in pesticides or agricultural inorganic. Cadmium can bind to intracellular metallothionein and can accumulate in the kidneys and liver. This study aims to determine the effect of exposure to pesticides on cadmium levels in farmers' blood samples.Method: This study was an observational analytic study with a cross sectional approach. The study population was farmers who actively used pesticides in Cangar. The sample selection uses purposive sampling technique. The research sample was farmers who met the criteria and actively sprayed pesticides at RT. 03 and RT 04, RW. 01 Cangar, Bumi Aji, Batu. Data collection using questionnaires and examination of cadmium metal levels in blood samples using AAS (Atomic Absorption Spectrophotometer).Results: The statistical test of this study used the Mann-Whitney Test. The influence of the frequency of pesticide administration on cadmium levels in farmers blood samples showed no significant difference between groups (p = 0, 665). The frequency of administration of the results of cadmium levels has values KPR and KPT (25,4 μg / L; 406,4 μg / L). The effect of exposure duration on cadmium levels in farmers blood samples showed no significant differences between groups (p = 0, 361). The duration of exposure to the results of cadmium levels has KPR dan KPT (9,3 μg / L; 140,1 μg / L) values. The effect of working period on cadmium levels in the blood sample of farmers showed no significant difference between groups (p = 0, 899). The working period for cadmium levels has KPR and KPT (13,4 μg / L; 110,8 μg / L).Conclusion: There were no significant differences between groups related to the effect of the frequency of pesticide administration, the influence of the length of pesticide spraying and the working period of farmers on the blood cadmium level of farmers